Medical and pharmaceutical workers as special subjects of crime (art. 140 Criminal Code of Ukraine) - Лихова, Софія Яківна; Монастирський, Назарій Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Issues of comparison of medical and pharmaceutical workers as subjects of proper execution of their professional obligations are examined. The necessity of exact differentiating of terms «medical» and «pharmaceutical» workers is emphasized in qualification of actions which are provided by Article 140 of the Criminal Code of Ukraine.